2011
DOI: 10.1111/j.1570-7458.2011.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex pheromone emission on the attraction of Lobesia botrana

Abstract: WileyVacas González, S.; Alfaro Cañamás, C.; Zarzo Castelló, M.; Navarro-Llopis, V.; Primo Millo, J. (2011) Rubber septa are the most common pheromone dispensers used in monitoring traps, but often 28 dispenser performance is not optimized. The key to improve methods based on pheromones as 29 attractants (monitoring, mass trapping, or 'attract and kill') is to know the optimum emission 30 interval, because release rates can strongly affect the attraction. In this work, five levels of 31 pheromone load with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…In pest management, volatile sex pheromones are commonly applied to trap and monitor lepidopteran and coleopteran pest species and to disrupt their communication (Arakaki et al 2008, Vacas et al 2011. Jewett and Carpenter (1998) hypothesized that sex pheromones could also be used to monitor the occurrence and density of natural pest enemies, including parasitoids, and to assess the optimal timing of additional releases.…”
Section: Discussionmentioning
confidence: 99%
“…In pest management, volatile sex pheromones are commonly applied to trap and monitor lepidopteran and coleopteran pest species and to disrupt their communication (Arakaki et al 2008, Vacas et al 2011. Jewett and Carpenter (1998) hypothesized that sex pheromones could also be used to monitor the occurrence and density of natural pest enemies, including parasitoids, and to assess the optimal timing of additional releases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the lobesia borana female could release about 0.3 ng h −1 sex pheromone 16 and we assume that it could release about 0.3 ng h −1 × 2 h × 7 d ≈ 0.0042 μ g wk −1 . The optimum release rate for lobesia borana in the field had been reported as 2800 μ g wk −1 (400 μ g d −1 ) 17 . Those results suggested that the artificial sex pheromone released from dispenser should reach approximately 6.6 × 10 5 times of the female's could outcompete female moth.…”
Section: Discussionmentioning
confidence: 99%
“…Pheromone-baited traps are employed to detect adult males of this pest and to monitor them, while mating disruption techniques have been extensively used for population control (Witzgall et al , 2005; Vacas et al , 2011); capture of the males figuring among the best means of monitoring adult phenology throughout the season (Anshelevich et al , 1994; Witzgall et al , 2000; Anfora et al , 2005). Control of eggs and young larvae by chemical treatments or insecticides containing Bacillus thuringiensis toxins (Ruiz de Escudero et al , 2007), or regulation by natural enemies (Xuéreb & Thiéry, 2006) have also been described.…”
Section: Introductionmentioning
confidence: 99%